Modelagem de inversores em fluxo de potência considerando suporte de potência reativa como serviço ancilar na distribuição - Sarmiento, Jonattan Emanuel (2016)
In recent years there has been a great increase in the use of distributed generators. This occurred not only by advances in production technologies of small generators and frequency inverters, but also by the benefits that brings to the distribution systems and the incentive policies. In the analysis of these systems is essential to calculate the power flow and properly solve it and the modeling of the inverter should be reviewed together with its implementation in the method employed, attempting to the fact that the inverters are beginning to use advanced functions that can to provide ancillary services. In this work the modelling of inverter with advanced functions such as Basic Intelligent Volt-Var Control (BIVV) and Intelligent Volt-Var With Hysteresis (IVVH) are reviewed, therefore it is propose methods the implements this models in the method sweep. In proposal implementation it is use of elements of the sensitivity matrix of nodes PV defined in the compensation method. In the analyzed cases, the implementations were effectiveness achieving solutions in convergent values and in accordance to the control strategies. In the results of simulations there were differences in the operating points of the inverter acting on a node of the distribution system comparing the different modeling analyzed in different system load conditions and different levels of active power supply. When comparing the voltage profiles of the various modeling, in general notice that there is a greater variation when it has large reactive power capacity. If in the future of distributed generation evolve to provide reactive support as the ancillary service, it shall be careful properly modelling the inverter avoiding mistaken results that will affect the plans of the concessionaires.